A paradigm shift in trainee confidence in teledermatology and virtual working during the COVID‐19 pandemic: results of a follow‐up UK‐wide survey. (1st April 2021) - Lowe, A.; Pararajasingam, A.; Goodwin, R. G.
Summary: The entire landscape of dermatology service provision has been transformed by the current SARS‐CoV‐2 (COVID) pandemic, with virtual working having become the new norm across the UK. A pre‐pandemic UK‐wide survey of dermatology registrars in training demonstrated a huge shortfall in trainee confidence in their teledermatology skills, with only 15% feeling even slightly confident, while 96% of trainees surveyed felt that more teaching in this area was needed. We carried out a follow‐up trainee survey during the COVID‐19 pandemic, which showed that the sudden thrust into virtual working had achieved dramatic gains in trainee confidence, propelling the percentage of trainees that now felt slightly confident to 58%. However, the shortfall remains, as does the pressing need to incorporate teledermatology into the trainee teaching timetable.